New school Japanese - English dictionary - Mashuda, K. (Kenkyusha, 1968)
It offers detailed coverage of Japanese vocabulary, giving headwords and examples in both romanized and script form, along with thousands of examples that help you find the translation you need quickly and easily. Translations for each of the over 40,000 entries are clear and concise, and offer guidance on grammar and usage, with slang, formal, and derogatory terms clearly marked. Additional supplements include a guide to grammar; help with pronunciation, numbers, and days of the week; and cultural information, covering topics such as the government, political parties, and historical periods of Japan.